Santoshi Mata Temple in Worli village - Mumbai Archive Project Team (Jio Institute, 2024)
Santoshi Mata Temple is dedicated to Santoshi Maa. She is a relatively new addition to the Koli pantheon of mother goddesses. The box-office success of the 1975 devotional movie Jai Santoshi Maa, which was based on the goddess and her devoted devotee Satyavati, is largely responsible for Santoshi Maa's recent rise to fame.